2019
DOI: 10.1016/j.schres.2018.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological functioning in early and chronic stages of schizophrenia and psychotic bipolar disorder

Abstract: Background: Neuropsychological impairment is common in schizophrenia and psychotic bipolar disorder. It has been hypothesized that the pathways leading to impairment differ between disorders. Cognitive impairment in schizophrenia is believed to result largely from atypical neurodevelopment, whereas bipolar disorder is increasingly conceptualized as a neuroprogressive disorder. The current investigation tested several key predictions of this hypothesis. Methods: Current neuropsychological functioning and estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 41 publications
2
17
1
1
Order By: Relevance
“…One subject was missing a positive scale score, so the average PANSS positive score across all schizophrenia participants was used for that subject. All individuals were administered the Screen for Cognitive Impairment in Psychiatry (SCIP), a brief (10-15 minute) measure of immediate and delayed verbal memory, verbal fluency, working memory and processing speed (for description of SCIP see (Menkes et al, 2018)). Scores from each sub-test were z-scored based on published norms (Purdon, 2005) and summed as a measure of cognitive ability.…”
Section: Clinical Data and Cognitive Datamentioning
confidence: 99%
“…One subject was missing a positive scale score, so the average PANSS positive score across all schizophrenia participants was used for that subject. All individuals were administered the Screen for Cognitive Impairment in Psychiatry (SCIP), a brief (10-15 minute) measure of immediate and delayed verbal memory, verbal fluency, working memory and processing speed (for description of SCIP see (Menkes et al, 2018)). Scores from each sub-test were z-scored based on published norms (Purdon, 2005) and summed as a measure of cognitive ability.…”
Section: Clinical Data and Cognitive Datamentioning
confidence: 99%
“…Today, a large body of literature demonstrates marked impairments in multiple cognitive domains in schizophrenia. Attention, memory and executive functions are among the most severely impaired domains Heinrichs, 2005;Heinrichs & Zakzanis, 1998;Menkes, Armstrong, Blackford, Heckers, & Woodward, 2019). Also in bipolar disorder cognitive impairments are widely reported, particularly in many of the same cognitive domains as in schizophrenia; i.e.…”
Section: Cognitive Functioning In Severe Mental Disordersmentioning
confidence: 99%
“…A meta-analysis of studies that included participants with schizophrenia and bipolar disorder in direct comparisons concluded that significant premorbid Cognitive subgroups in severe mental illness deficits are present in schizophrenia and that both disorders are characterized by cognitive decline after illness onset, with larger impairments in schizophrenia (Trotta, Murray, & MacCabe., 2015). Indeed, there is evidence for neurodevelopmental and neuroprogressive cognitive trajectories in both disorders (Menkes, Armstrong, Balckford, Heckers, & Woodward, 2019).…”
Section: Introductionmentioning
confidence: 99%